Finite element analysis of strains in a Blaberus cockroach leg during climbing - Kaliyamoorthy, S.; Zill, S.N.; Quinn, R.D.; Ritzmann, R.E.; Jongung Choi (2001 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2001)
The legs of animals and walking vehicles are subject to substantial changes in loading in climbing over obstacles. Sense organs (campaniform sensilla) on cockroach legs detect these loads through strains in the exoskeleton. Signals that might be sent by the sense organs during climbing were predicted by applying forces to a finite element model of the leg in directions determined from kinematic studies. The model included an accurate, three-dimensional reconstruction of the leg segment (trochanter) that contains an array of these sensors. Calculated strains generated at different phases of climbing suggest that some groups of sensors in the front leg, that show little activity in walking, are strongly activated in climbing. These groups could provide signals to aid in adapting walking patterns to the changing forces encountered in climbing.